PERAN GURU DALAM MEMBENTUK KECERDASAN VISUAL SPASIAL MELALUI FILM ANIMASI DI TAMAN KANAK KANAK ISLAM TERPADU QURROTA A'YUN BANDAR LAMPUNG TAHUN AJARAN 2024-2025 - SELVI AMALIA; YULI HABIBATUL IMAMAH (UNISAN JURNAL, 2025)
This study aims to identify teacher efforts in improving visual spatial intelligence of children aged 4-5 years through free drawing activities at Musi Indah Kindergarten (TK), Kandang Village, Seberang Bandar Lampug District, Kepahiang Regency. This type of research is qualitative descriptive. The methods used include educational, guiding, and evaluating approaches. In free drawing activities, teachers provide direction and stimulation that allows children to express their creativity. In addition, teachers play a role in guiding children during the drawing process, helping them understand shapes, colors, and composition. Evaluation is carried out to assess the development of children's visual spatial intelligence, which is reflected in their ability to create drawings. The results of the study showed that this effort was effective in improving children's visual spatial abilities, strengthening their imagination, and increasing their confidence in expressing themselves. These findings emphasize the importance of the role of teachers in supporting the development of visual spatial intelligence through fun activities.